The highlights in the 23rd Annual Meeting of the Asian Society for Cardiovascular and the Thoracic Surgery - Tang, Suki X. (Journal of Thoracic Disease, 2015)
The 23rd Annual Meeting of the Asian Society for Cardiovascular and the Thoracic Surgery was held from May 11-14, 2015 in Hong Kong—the oriental Pearl.